2012
DOI: 10.1051/0004-6361/201219085
|View full text |Cite
|
Sign up to set email alerts
|

The dominant role of mergers in the size evolution of massive early-type galaxies sincez ~  1

Abstract: Aims. The role of galaxy mergers in massive galaxy evolution, and in particular to mass assembly and size growth, remains an open question. In this paper we measure the merger fraction and rate, both minor and major, of massive early-type galaxies (M ≥ 10 11 M ) in the COSMOS field, and study their role in mass and size evolution. Methods. We used the 30-band photometric catalogue in COSMOS, complemented with the spectroscopy of the zCOSMOS survey, to define close pairs with a separation on the sky plane 10 h … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
67
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(80 citation statements)
references
References 148 publications
(257 reference statements)
11
67
2
Order By: Relevance
“…Some of the recent applications heavily relying on accurate photoz are: the cosmic time evolution of galaxy properties [e.g., 6] or the search of primordial galaxies [e.g., 7]; the study of the relation between galaxy properties and their dark matter halos [e.g., 8] or cluster identifications [e.g., 9]. Galaxy environment or galaxy pairs evolution can also be investigated with photo-z [e.g., [10][11][12], although with a limited precision [e.g., 13,14]. Similarly, photo-z are used for studying the evolution of galaxies hosting an Active Galactic Nucleus (AGN) [e.g., 15] or more peculiar objects [e.g., Blazars: 16].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the recent applications heavily relying on accurate photoz are: the cosmic time evolution of galaxy properties [e.g., 6] or the search of primordial galaxies [e.g., 7]; the study of the relation between galaxy properties and their dark matter halos [e.g., 8] or cluster identifications [e.g., 9]. Galaxy environment or galaxy pairs evolution can also be investigated with photo-z [e.g., [10][11][12], although with a limited precision [e.g., 13,14]. Similarly, photo-z are used for studying the evolution of galaxies hosting an Active Galactic Nucleus (AGN) [e.g., 15] or more peculiar objects [e.g., Blazars: 16].…”
Section: Introductionmentioning
confidence: 99%
“…Qu et al (2017) and Lagos et al (2018b) studied the impact of mergers on mass assembly and angular momentum on the EAGLE galaxies. The authors found that the reference model is able to reproduce the observed merger rates and merger fractions of galaxies at various redshifts (Conselice et al 2003;Kartaltepe et al 2007;Ryan et al 2008;Lotz et al 2008;Conselice et al 2009;de Ravel et al 2009;Williams et al 2011;López-Sanjuan et al 2012;Bluck et al 2012;Stott et al 2013;Robotham et al 2014;Man et al 2016). Thus EAGLE can be used to study the effect of mergers on the σ sSFR -M ⋆ relation.…”
mentioning
confidence: 99%
“…For the redshift range probed by SHELS, this rate translates to ∼ 0.05 dex increase in stellar mass. Newman et al (2012b) estimate the growth rate for less massive galaxies (M * > 10 10.7 M ⊙ ) at z < 1 by identifying companions of massive quiescent host galaxies (see also López-Sanjuan et al 2012). Adopting a merger timescale of 1 Gyr and a ∆t = 4 Gyr, Newman et al (2012b) estimate a growth of ∼ 0.1 dex for galaxies with M * ∼ 10 10.7 M ⊙ .…”
Section: The Stellar Growth Ratementioning
confidence: 99%